Audit Manajemen Sumber Daya Manusia dalam Upaya Peningkatan Efektivitas Kinerja Perangkat Desa di Kantor Desa Bumi Jaya Kabupaten Okus - Kontesa, Melia; Nurfadila, Nova; Kariya, Hetty; Sapitri, Hera; Anggini, Marcha Dwi; Destiarini, Destiarini (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the implementation of human resource management audits to improve the performance effectiveness of village officials at the Bumi Jaya Village Office. A human resource management audit is a systematic evaluation activity to assess the effectiveness and efficiency of human resource management functions, such as planning, recruitment, training, performance appraisal, and compensation. The research method used was descriptive qualitative, with data collection techniques including interviews, observation, and documentation with village officials and related parties. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of human resource management audits at the Bumi Jaya Village Office is still suboptimal. Several aspects, such as training and performance appraisal, require improvement to align with effective management standards. Through the implementation of human resource audits, the village government can identify weaknesses in the human resource management system and improve the performance and competency of village officials. The ongoing implementation of human resource audits is expected to increase the effectiveness of village officials, improve the quality of public services, and help achieve village development goals optimally